COVID-19 vaccine uptake among people who inject drugs in Tijuana Mexico - Harvey-Vera, Alicia; Munoz, Sheryl; Artamonova, Irina; Abramovitz, Daniela; Mittal, Maria Luisa; Rosales, Cecilia; Strathdee, Steffanie A.; Rangel, Maria Gudelia (Frontiers in Public Health, 2022)
Background: SARS-CoV-2 prevalence is elevated among people who inject drugs (PWID). In Tijuana, Mexico, COVID-19 vaccines became available to the general population in June 2021, but uptake among PWID was <10%. We studied COVID-19 vaccine uptake among PWID in Tijuana following implementation of a pop-up vaccination clinic. Methods Beginning in October, 2020, PWID in Tijuana aged ≥18 years were enrolled into a longitudinal cohort study. At baseline and semi-annually, participants underwent interviewer-administered interviews on health behaviors and COVID-19 exposures through April 5, 2022. From June 21—September 20, 2021, staff referred PWID to a temporary COVID-19 vaccine pop-up clinic that was coincidentally established near the study office. Participants attending the clinic completed a short interview on barriers to vaccination and were offered facilitated access to free Janssen® COVID-19 vaccine. All participants were reimbursed 5 for this interview, regardless of whether or not they chose to be vaccinated. Poisson regression was used to evaluate the effect of the pop-up clinic on COVID-19 vaccination uptake, controlling forpotential confounders. Results Of 344 participants, 136 (39.5%) reported having received at least one COVID-19 vaccine dose during the 10 months follow-up period, of whom 113 (83.1%) received vaccine at the pop-up clinic and 23 (16.9%) elsewhere. One third of those receiving COVID-19 vaccine during the pop-up clinic were previously vaccine hesitant. Attending the pop-up clinic was independently associated with higher rates of COVID-19 vaccination Adjusted Rate Ratio (AdjRR: 9.15; 95% CI: 5.68–14.74). Conclusions We observed a significant increase in COVID-19 vaccine uptake associated with attending a temporary pop-up vaccine clinic in Tijuana suggesting that efforts to improve vaccination in this vulnerable population should include convenient locations and staff who have experience working with substance using populations. Since COVID-19 vaccination rates remain sub-optimal, sustained interventions to increase uptake are needed.